Algebraic expression #8

mathwannabe

Junior Member
Joined
Feb 20, 2012
Messages
122
Hello everybody :D

I have been doing pretty good with algebra lately, but I have stumbled upon a problem I can't seem to wrap myself around.

1) \(\displaystyle \dfrac{a}{b^3-1}-\dfrac{b}{a^3-1}=?,\) IF \(\displaystyle a+b=1\)

I get to:

\(\displaystyle \dfrac{(a+b)(b^2-a^2)}{(2a+b)(a+2b)}=\)

\(\displaystyle =\dfrac{(a+b)^2(b-a)}{(2a+b)(a+2b)}\)

I tried it a few times, but no matter what I always end up here, which is a dead end for me.

Any help/hint will be greatly appreciated.
 


I get to:

\(\displaystyle \dfrac{(a+b)(b^2-a^2)}{(2a+b)(a+2b)}=\)

\(\displaystyle =\dfrac{(a+b)^2(b-a)}{(2a+b)(a+2b)}\)


Whoops... he he, never mind that, he he... I guess I'm just to tired, if that's not the case, I better go check my head ;)
 
Last edited:
Hello everybody :D

I have been doing pretty good with algebra lately, but I have stumbled upon a problem I can't seem to wrap myself around.

1) \(\displaystyle \dfrac{a}{b^3-1}-\dfrac{b}{a^3-1}=?,\) IF \(\displaystyle a+b=1\)



Another path:

\(\displaystyle \dfrac{a}{b^3-1}-\dfrac{b}{a^3-1}\)

\(\displaystyle = \ \dfrac{a}{(b-1)(b^2+b+1)}-\dfrac{b}{(a-1)(a^2+a+1)}\)

\(\displaystyle = \ \dfrac{-1}{b^2+b+1}-\dfrac{-1}{a^2+a+1}\)

\(\displaystyle = \ (-1)\left [\dfrac{a^2 - b^2 + a - b}{(b^2+b+1)(a^2+a+1)}\right ]\)

\(\displaystyle = \ \dfrac{2(b - a)}{(b^2+b+1)(a^2+a+1)}\)

expanding denominator

\(\displaystyle = \ \dfrac{2(b - a)}{a^2b^2+b^2 + a^2 + 2ab + a + b + 1}\)

\(\displaystyle = \ \dfrac{2(b - a)}{(a^2b^2+3)}\)


I don't see anymore useful reduction....



 
Last edited by a moderator:
Top